Página 89 Manuscript selection-reviewing of the articles and instructions for authors - Madariaga, Aura Lissete; Instituto de investigaciones Químicas y Biológicas, Facultad de Cienias Químicas y Farmacia. USAC (Universidad de San Carlos de Guatemala, 2015)
Manuscript selection-reviewing of the articles and instructions for authors